LITERATURE REVIEW: THE EFFECT CARDIOPULMONARY RESUSCITATION (CPR) IN THE PRONE POSITION ON HEMODYNAMIC STATUS IN CARDIAC ARREST PATIENT WITH COVID-19 - Linda Widyarani (Jurnal Keperawatan Malang, 2021)
Background: Cardiac arrest is the sudden cessation of cardiac activity so that the victim becomes unresponsive, with no normal breathing and no signs of circulation. Early initiation of CPR is associated with improved outcomes for cardiac arrest. Cardiac arrest in the prone position may be more challenging to treat because care providers trained in conventional CPR, may not be familiar with CPR in the prone position. Objective: The aim of this systematic review is to provide an overview of current evidence regarding the effect of CPR in the prone position, in hemodynamic status patient’s with Covid-19. Method: In this systematic review, we searched PubMed, EBSCO, Science Direct dan Google Scholar databases for articles that evaluated the effect of CPR in the prone position, in hemodynamic status patient’s with Covid-19. This literature review focuses on randomized control trial, cohort study dan qualitative study, published in the English language from 2018 to 2020. Result: All studies published up to Desember 2020 including cardiac arrest or CPR in the prone position were included. Of the 26 articles located, 9 articles were included: 5 review articles, 4 clinical guidelines in which prone CPR was mentioned. Conclusion: CPR in the prone position is a reasonable alternative to supine CPR when the latter cannot be immediately implemented, and the airway is already secured. Familiarizing clinicians with CPR and defibrillation in the prone position may improve CPR performance in the prone position. Keyword : CPR, prone position, Covid-19, hemodynamic status